Analysis of Anthropometric Parameters of the Craniofacial Region in Children with Scoliosis (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Scoliosis is a lateral curvature of the spine, which is dangerous for severe complications, especially for a growing child's body. In 80% of the number of people with this pathology, idiopathic scoliosis is diagnosed. Scoliosis is a disease that is not only accompanied by curvature of the spine, but also causes various deformities in other parts of the child's body.